Group Bonding and Effectiveness: Cohesion's Moderating Role and Leaders' Relationship Mediating Role. (August 2021) - Klang, Motti; Luria, Gil
The role of group bonding (friendship ties among group members) and the relationships between group members and the formal leader in the prediction of effectiveness was studied. A theoretical mediated-moderation process model was tested. The model was examined through a longitudinal research with 91 natural groups, that included social network analysis to capture the relationship between group members and a leadership differentiation measure to revel their relationship with the leader. As hypothesized, group bonding predicted group effectiveness, group cohesion mediated only one dimension of group effectiveness, and leadership differentiation moderated this process.